Construction of coconut shell column for the enhancement of expansive soil - Ng, Jun Shen; Muzamir, Hasan; Nurrul Nisya, Anuar (Peter the Great St. Petersburg Polytechnic University, 2024)
The authors used the crushed coconut shell to make granular columns which were obtained from the market area of Kuantan, Pahang. The coconut was crushed into a similar size of coarse aggregate for the replacement of non-renewable resources like sand and gravel. From its general properties, a coconut shell is hard and can withstand a certain value of exerted value regardless of compression or tension. Besides, the coconut shell is an agricultural product and is found abundantly after human consumption. For this research, the stone-column method was used. The installation of a single coconut shell column was implemented through the Vibro-replacement technique on the soft clay soil. Before accessing the shear strength parameters, the evaluation of the physical and mechanical properties of coconut shells and kaolin was executed via the appropriate geotechnical laboratory approaches. The shear strength parameters were analysed with the control and reinforced specimens through the Unconfined Compression Test (UCT). For the shear strength value, the average value from 4 specimens was utilized as the final value. A total of 16 samples were constructed for all the specimens, reinforced design comprised of 13 mm column diameter, and column heights of 60 mm and 80 mm were categorized as partially penetrated columns while 100 mm was a fully penetrated column. The highest shear strength improvement was recorded when the column height was 100 mm, resulting in 28.51 %, whereas the least was recorded when 60 mm of height was constructed, only 17.28 %. Conclusively, the positive results of shear strength improvements were yielded by the utilization of coconut shells and proved that it was practical and economical.